Monte Carlo investigation of grain size dependence of magnetic properties - Laosiritaworn Y. (2014)
In this work, Monte Carlo simulation was used to study the grain size dependence of ferromagnetic properties. The Ising model and the spin flip algorithm were used to observe the grain size effect on both static and dynamic properties. From the results, it was found that the competition between the grain size and cluster size of same spins (which is controlled by the dipolar interaction) plays a crucial role on ferromagnetic behavior. For instance, at a particular grain size, the ferromagnetic phase transition shifts to a lower temperature with increasing the dipolar magnitude. On the other hand, by increasing the grain size, the ferromagnetic hysteresis can either be enhanced or deteriorated depending on the magnitude of the dipolar interaction, where to some extent agree with applicable experiments. This therefore suggests a way to tune the ferromagnetic properties by varying the grain size or the dipolar magnitude. © 2009 IEEE.